Volatility modelling and VaR: The case of Bitcoin, Ether and Ripple - Jakub Ječmínek; Gabriela Kukalová; Lukáš Moravec (DANUBE: Law, Economics and Social Issues Review, 2020)
Since Bitcoin introduction in 2008, the cryptocurrency market has grown into hundreds-of-billion-dollar market. The cryptocurrency market is well known as very volatile, mainly for the fact that the cryptocurrencies have not the price to fall back upon and that anybody can join the trading (no license or approval is required). Since empirical literature suggests that GARCH-type models dominate as VaR estimators the overall objective of this paper is to perform comprehensive volatility and VaR estimation for three major digital assets and conclude which method gives the best results in terms of risk management. The methods we used are parametric (GARCH and EWMA model), non-parametric (historical VaR) and Monte Carlo simulation (given by Geometric Brownian Motion). We conclude that the best method for value-at-risk estimation for cryptocurrencies is the Monte Carlo simulation due to the heavy diffusion (stochastic) process and robustness of the results.
Keywords: 330; Cryptocurrency; Volatility; Value-at-risk; VaR; Geometric Brownian Motion; GARCH